The Effect of Hand Puppet Game and Cold Compress on the Reduction of Pain and Anxiety Levels in Preschool Age Children Undergoing Infusion in the Pediatric Care Room at Sumbawa Hospital - Yasinta Aloysia Daro; Alfia Safitri; Evie Sulahyuningsih (Journal of Health Policy and Management, 2021)
Background: The infusion procedure was the most traumatic experience and can cause anxiety and pain for more than 50% of pediatric patients during hospitalization. This study was to determine the effect of hand puppet game and cold compress on pain and anxiety of preschool age children undergoing infusion.Subjects and Method: This study used a quasi-experimental research design with the type of non-equivalent control group posttest-only design. It was conducted in the Pediatric Care Room at Sumbawa Hospital in July-September 2020. The total number of respondents who were hospitalized in the Pediatric Care Room at Sumbawa Hospital selected by consecutive sampling. They were divided into two, 38 people in each intervention and control group. The intervention group was given cold compress on the infusion area and the hand puppet game, while the control group was given treatment according to hospital standards. The dependent variables of the study were pain level and anxiety level, while the independent variables included hand puppet game and ice pack (cold compress). In addition, the instruments used were pain and anxiety instruments. Data analysis was performed using the Mann-Whitney test.Results: Based on the results of the Mann-Whitney test, there was a change of pain levels (p<0.001) and anxiety levels (p<0.001) after receiving hand puppet game and cold compress during infusion compared to children with normal treatment.Conclusion: Hand puppet game and cold compress administration can be applied to reduce pain and anxiety levels in preschool age children during the infusion procedure.Keywords: children, distraction, anxiety, pain, infusionCorrespondence: Alfia Safitri. Faculty of Health, Universitas Samawa, Jl. Lintas Sumbawa Bima Km 03 Sumbawa Besar. Email: fiasafitri90@gmail.com. Mobile: 082341612302.Journal of Health Policy and Management (2021), 06(02): 148-153https://doi.org/10.26911/thejhpm.2021.06.02.07